Interpersonal communication as a solution for resolving diplomatic conflicts in the Malay sultanates - Noor Muhammad, Salmah Jan (Dewan Bahasa dan Pustaka, 2018)
Interpersonal communication is an important element in the management of a government organization. In diplomatic relations, interpersonal communication tests an individual’s or a group’s ability to convey the message of peace. The ability to convey information clearly and thus avoiding misunderstanding, especially in resolving conflicts that may occur, builds trust among governments. Without skill in interpersonal communication, it becomes difficult for a government to maintain existing relations, or build new ones. This research was carried out to (i) analyse the interpersonal communication implemented by the Malay Sultanates as the main mechanism in resolving diplomatic conflicts, and (ii) explain the implications of the implementation of interpersonal communication in resolving conflicts among kingdoms. Data was collected through library research, and this discussion focuses on Hikayat Hang Tuah and Al-Tarikh Salasilah Negeri Kedah as the primary material. The findings of this study show that the sending of envoys was an effective strategy of interpersonal communication in solving conflicts that arose, whether in terms of existing or new diplomatic relations. These envoys employed various strategies in their interpersonal communication, which were key to the success of their missions. The findings also show that the administration and government of a kingdom stabilized with the development of its economy, politics, culture and society.